Who is in charge? An analysis of waste electrical and electronic equipment management in Brussels - Jean Mansuy; Philippe Lebeau; Sara Verlinde; Cathy Macharis (Brussels Studies, 2022)
The management of waste electrical and electronic equipment (WEEE) underperforms in the Brussels-Capital Region. This lower performance is partly related to the collection of such WEEE through unregistered channels. Using a relational approach, this study aims to understand the roles of WEEE management stakeholders. It reveals the existence of a market-based network, conflicting with the official network centralised around Recupel. It also highlights how the choices of consumers and retailers channel WEEE in either subnetwork. Based on these results, we suggest solutions to limit unregistered channels, either by further integrating the market-based subnetwork in the official one or by influencing the behaviour of consumers’ and retailers.